2018
DOI: 10.3758/s13428-018-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

Norms of conceptual familiarity for 3,596 French nouns and their contribution in lexical decision

Abstract: In the last decade, research has shown that word processing is influenced by the lexical and semantic features of words. However, norms for a crucial semantic variable-that is, conceptual familiarity-have not been available for a sizeable French database. We thus developed French Canadian conceptual familiarity norms for 3,596 nouns. This enriches Desrochers and Thompson's (2009) database, in which subjective frequency and imageability values are already available for the same words. We collected online data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…At the end of this assessment, participants were asked to assess, through the exact same online format, the psycholinguistic characteristics of the 270 words, namely concreteness, imageability, conceptual familiarity, and age of acquisition. The instructions for the different variables were either adapted on the basis of original instruction taken from previous published studies (e.g., Bonin et al, 2003a,b;Ferrand et al, 2008;Chedid et al, 2019b) and are available at the Appendix C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of this assessment, participants were asked to assess, through the exact same online format, the psycholinguistic characteristics of the 270 words, namely concreteness, imageability, conceptual familiarity, and age of acquisition. The instructions for the different variables were either adapted on the basis of original instruction taken from previous published studies (e.g., Bonin et al, 2003a,b;Ferrand et al, 2008;Chedid et al, 2019b) and are available at the Appendix C.…”
Section: Methodsmentioning
confidence: 99%
“…Concreteness refers to the degree to which words refer to people, places and things that can be seen, heard, touched, smelled, or tasted, and imageability is defined to the ease with which it is possible to form a mental image associated with a word (Bonin et al, 2003a). Words processing also appeared to depend on concepts' age of acquisition (AoA; e.g., the age at which a word was learned) or conceptual familiarity (e.g., the degree to which people come in contact with or think about a concept; e.g., Bonin et al, 2003b;Ferrand et al, 2008;Kuperman et al, 2012;Chedid et al, 2019b). Interestingly, while Vergallito et al (2020) reported imageability as a stronger predictor of Italian word processing reaction times, studies conducted in other languages (e.g., Canadian French: Chedid et al, 2019a;English: Connell and Lynott, 2012;Dutch: Speed and Brysbaert, 2020) revealed that the effect of perceptual strength was even more important than the effect of well-known psycholinguistic variables, such as concreteness and imageability, suggesting that the importance of these variables could be influenced by crosslinguistic differences.…”
Section: Introductionmentioning
confidence: 99%
“…There are also sets of musical stimuli used to study musical expectancy, which often consist of series of chord progressions (Koelsch, Gunter, Wittfoth, & Sammler, 2005). Outside of the realm of music, normed stimulus sets are quite commonfor example, there are stimulus sets of visual stimuli representing different emotions (Kurdi, Loano, & Banaji, 2017;Lang, Bradley, & Cuthbert, 2008), everyday objects (Snodgrass & Vanderwart, 1980;Tranel, Logan, Frank, & Damasio, 1997) or unique objects (Tranel, Enekwechi, & Manzel, 2005); sets of words in English (Deyne, Navarro, Perfors, Brysbaert, & Storms, 2018;Scott, Keitel, Becirspahic, Yao, & Sereno, 2018) and other languages (Chedid et al, 2018); and sets of voices (Darcy & Fontaine, 2019;Zäske, Skuk, Golle, & Schweinberger, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese, French, Icelandic, Italian, Kannada, Spanish and Turkish (Álvarez & Cuetos, 2007;Bangalore et al, 2022;Chalard et al, 2003;Chedid et al, 2019;Göz et al, 2017;Li et al, 2022;Liu et al, 2011;Lotto et al, 2010;Montefinese et al, 2019;Perez & Navalon, 2005;Pind et al, 2000;Pind & Tryggvadóttir, 2002). Recently, these AoA measures have also been found to be correlated (r = .29-.91) between 35+ languages, including Arabic, Chinese, Gaelic, English and Persian for pictures of objects and actions (Łuniewska et al, 2016, 2019), indicating the reliability and generality of adult ratings for AoA across cultures and languages.…”
Section: The Mapping Theorymentioning
confidence: 99%